The most common treatment under general anaesthesia in hospital USM: a paediatric case study from 2015 To 2018 - W Ahmad, Wan Muhamad Amir; Samsudin, Norsamsu Arni; Aleng, Nor Azlida; Nizam Akbar, Nurul Asyikin; Mohamad Ghazali, Farah Muna; Ghazalli, Nur Fatiha; Abdul Halim, Nurfadhlina; Mohd Noor, Nor Farid; M. Nashir, Muhamad Najib; Mohd Ibrahim, Mohamad Shafiq (New York Business Global LLC, 2022)
Introduction: General anaesthesia (GA) dental care is one of the clinical strategies used to treat non-cooperative those, patients with chronic medical problems or with specialised and comprehensive treatment by some paediatric dentists. Objective: The purpose of this retrospective research was to analyse cases of general anaesthesia in paediatric dentistry at Hospital Universiti Sains Malaysia (USM), Kubang Kerian, Kelantan. Methods: A total of 298 patients reports were collected for data processing from 2015 to 2018. Results: About 54% of patients in the Malay ethnic community were male and the mean age was 5 years. The highest treatment is on the fissure sealant restoration, 100(33.6%) and follows by extraction of deciduous teeth 218(73.2%). The lowest treatment was found in Sandwich Technique Restoration 1(0.3%), excision of chronic mucocele, which is about 2(0.7%), and the treatment based on GIC Fuji IV 2(0.7%). The next analysis is focusing on the type of treatment. The result from multiple responses shows that patients with a combination of three treatment having 61%, this is the highest percentage. While patients with four types of treatment are the second highest, 59 cases or 25.4% and the third highest comes from the category of patients with two types of treatment. Conclusion: An annual rise in referred cases for dental care under GA has been observed. it is believed that the number of patients receiving dental treatment under GA is likely will continue to show an upward trend, and for the specific finding it was found that the extraction deciduous teeth are the highest case which is about 31.2%, fissure sealant restoration about 14.3% and stainless steel crown which is 13.3%.